2003
DOI: 10.1053/jhep.2003.50147
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in the relationship between hepatitis C infection and iron stores

Abstract: Black race and increased hepatic iron stores predict poor response to interferon treatment for chronic hepatitis C virus (HCV) infection. We tested the hypothesis that these 2 observations are linked by investigating whether HCV-infected African-Americans have increased iron stores relative to uninfected persons. Using data from the third National Health and Nutrition Examination Survey (NHANES III), we determined the risk of having increased iron stores, defined as elevation of both serum ferritin and transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…Racial differences may occur in the performance of tests to screen for HCV-related liver fibrosis, just as racial differences occur in spontaneous clearance of HCV infection 9,25 and response to interferon alfa therapy for chronic hepatitis C. 26,27 Slower natural history of HCV-related fibrosis has also been reported in African Americans. 28,29 These data underscore the importance of validating screening tests in a variety of clinical settings.…”
Section: Discussionmentioning
confidence: 92%
“…Racial differences may occur in the performance of tests to screen for HCV-related liver fibrosis, just as racial differences occur in spontaneous clearance of HCV infection 9,25 and response to interferon alfa therapy for chronic hepatitis C. 26,27 Slower natural history of HCV-related fibrosis has also been reported in African Americans. 28,29 These data underscore the importance of validating screening tests in a variety of clinical settings.…”
Section: Discussionmentioning
confidence: 92%
“…The causes of racial variation are still unclear. Some factors, like cytokine production and hepatic iron level, have been considered as the origin of inter-ethnic differences in prior investigations [41,42]. Since the strong associations of IL28B gene polymorphisms with HCV clearance have been demonstrated, SNPs near the IL28B gene are thought to be the leading cause of racial variation of HCV clinical outcomes [43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the association between HCV infection and elevated hepatic iron stores was markedly more pronounced in African Americans (odds ratio: 17.8; 95% CI: 5.1-63) than in other races/ethnicities. 35 However, it is not clear whether the presence of elevated iron stores is a causative factor or a just a marker of poor response to therapy. Interestingly, a retrospective study of prison inmates who underwent directly observed interferon and ribavirin therapy for genotype 1 HCV showed no differences in SVR.…”
Section: Racial Disparities In the Treatment Of Liver Diseasementioning
confidence: 99%